NC State's Principal Leadership Academies: Context, Challenges, and Promising Practices. (March 2019) - Fusarelli, Bonnie C.; Fusarelli, Lance D.; Drake, Timothy A.
Developing effective educational leaders is fundamentally and irrevocably an interpersonal, relational process—one that requires face-to-face contact, deep thought, deliberation, reflection, engagement, and interaction. It requires cultivation of the habits of heart, mind, and soul. For nearly a decade, the faculty at North Carolina State University (NCSU) have focused on dramatically improving principal preparation. This article explores the initial design of the program, its key features and how they have evolved, processes established for continuous improvement, major challenges faced and approaches to addressing these challenges, and recent program initiatives.